ANALISIS NILAI-NILAI KE-INDONESIAAN AKIBAT PENGARUH GLOBALISASI - Wini Jihan Firliani; Dita Fadila Aida Fitri; Jingga Puspita; Sindi Novitasari; Ainawa Hasna Haura; Yoga Fernando Rizqi (CV. ADIBA AISHA AMIRA, 2024)
Globalization has a significant impact on Indonesian values, influencing various aspects of Indonesian people's lives. This research analyzes changes in Indonesian values ​​due to the influence of globalization using descriptive analysis methods from various data sources. The results of the analysis show a complex transformation in traditional values ​​such as mutual cooperation, kinship, and cultural diversity, with several aspects experiencing weakening due to the domination of foreign culture through media and technology. However, there are also positive aspects such as increasing access to information which can strengthen Indonesian identity through a broader understanding of culture and history. Thus, globalization has a complex impact on Indonesian values ​​which presents challenges and opportunities that need to be managed wisely in the global era.